Disturbance In Long Distance Gamma Coherence In Bipolar Disorder - Özerdem, Ayşegül; Güntekin, Bahar; Saatçı, Ertuğrul; Tunca, Zeliha; BAŞAR, EROL (Pergamon-Elsevier Science Ltd, The Boulevard, Langford Lane, Kidlington, Oxford Ox5 1Gb, England, 2010)
The aim of this study was to investigate long distance event-related gamma (28-48 Hz) coherence in mania before and after valproate monotherapy. Gamma coherence in response to visual oddball paradigm in ten medication-free, manic patients was studied before and after six weeks of valproate monotherapy in comparison to ten controls. Inter-hemispheric F(3)-F(4), C(3)-C(4), T(3)-T(4), T(5)-T(6), P(3)-P(4), O(1)-O(2) and intra-hemispheric F(3)-P(3), F(4)-P(4), F(3)-T(5), F(4)-T(6), F(3)-O(1), F(4)-O(2), C(3)-O(1), C(2)-O(4) electrode pairs were included in the analysis. Repeated measures ANOVA revealed a significant difference between groups with regard to pre-treatment coherence values (p: 0.018). The coherence to the target stimuli at the right fronto-temporal location was significantly reduced by 35.41% in the patients compared to controls (p: 0.003). Patients showed significantly lower pretreatment coherence values in response to non-target stimuli compared to controls at the right frontotemporal (28.51%, p: 0.004), right fronto-occipital (23.71%, p: 0.024), and right centro-occipital (25.69%, p: 0.029) locations. After six weeks of valproate monotherapy, manic symptoms improved significantly. Post-treatment change in target and non-target coherence values was statistically non-significant. EEG coherence is a measure of functional connectivity in the brain. Event-related gamma oscillations are essential for brain electrical activity. The results show that acute mania presents right sided long distance connectivity disturbance, thus pointing to the potential importance of measuring oscillatory responses in the search for consistent neurobiological markers in such a complicated condition as bipolar disorder. (C) 2010 Elsevier Inc. All rights reserved.
Keywords: Bipolar disorder; Event-related oscillations; Gamma coherence; Mania; Neurocognitive functioning; Valproate; oscillatory responses; brain oscillations; alzheimer patients; visual-cortex; valproate; alpha; EEG; synchronization; generation; schizophrenia; Bipolar bozukluk; Olaya ilişkin salınımlar; Gama uyum; cinnet; nörobilişsel işleyişi; salınım tepkiler; beyin salınımlar; alzheimer hastaları; görsel korteks; alfa; senkronizasyon; nesil; şizofreni